Postoperative Multimodal Analgesic Effect of Gabapentin and Ketorolac with Acetaminophen after Remifentanil Infusion in Traumatic Maxillofacial Surgery - Pejman Pourfakhr; Reza Shariat Moharari; Farhad Etezadi; Khosro Barkhordari; Farsad Imani; Mohammad Reza Khajavi (Archives of Anesthesia and Critical Care, 2016)
Background: Pain control after traumatic maxillofacial surgery due to severity of pain and limitations of opioids use in these patients is of particular importance. The aim of this study was to evaluate the multimodal analgesic effect of oral gabapentin and intramuscular ketorolac in combination with intravenous acetaminophen for pain control after remifentanyl infusion in this surgery. Methods: This study was a randomized clinical trial (RCT) on 60 patients (18-45 yr old ASAI to II) undergoing traumatic maxillofacial surgery in Sina Hospital affiliated to Tehran University of Medical Sciences, Tehran, Iran from July 2014 to septamber 2015. The patients were randomly divided in 2 groups. Both groups received 1 gr (IV acetaminophen) 0.5 hour before the end of surgery. The Ketorolac group (n= 30) received 30 mg IM Ketorolac after induction of anesthesia and the Gabapentin group (n= 30) received 600 mg Gabapentin orally 30 minute before the induction of anesthesia. The pain severity score (assessed by VAS scale, the level of sedation (assessed by Ramsey scale), opioid requirement, nausea and vomiting was recorded in the postanestheisa care unit (PACU) and at 1-12-24 hours after surgery. For rescue pain management intravenous morphine was administered. Results: Sixty patients were enrolled in this study. Use of Ketorolac and Gabapentin declines the pain intensity, level of agitation and morphine requirement in the recovery room and early hours in the ward. Mean arterial pressure and heart rate changes were significantly lower in ketorolac group compared with gabapentin group in the recovery room (P< 0.05). Conclusion: The results of this study suggest that single intramuscular ketorolac in combination with intravenous acetaminophen can decline the pain intensity and opioid requirement with less nausea and vomiting and good hemodynamic control after traumatic maxillofacial surgery.